Financial development dynamic thresholds of financial globalization: evidence from Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
Purpose The issue of which financial initial conditions are necessary to materialize the benefits of financial globalization remains open to debate in the literature. In this paper, we try to put some empirical structure on the concept of financial threshold conditions in order to give policymakers guidance on the Kose et al. (2011) and Henry (2007) hypothesis. Its object is to assess if financial benefits of financial globalization are questionable until greater domestic financial development has taken place in African countries. Design/methodology/approach In framing the financial dimension in a more concrete and tractable manner, we examine the concerns of how domestic financial initial dynamics of depth (economic and financial systems), efficiency (banking and financial systems), activity (banking and financial systems) and size, play out in the financial development benefits of financial globalization. The estimation approach consists of assessing the impact of financial globalization through-out the conditional distributions of domestic financial development dynamics. Findings The introduction of previously missing financial dimensions into the debate generates a number of important findings. Only financial initial (threshold) conditions of size are necessary to materialize the benefits of financial globalization. While financial depth only partially validates the hypothesis, dynamics of efficiency and activity (credit) do not confirm the hypothesis. Practical implications Addressing the issue of surplus liquidity in African financial institutions could improve the benefits of financial size and potentially reverse the trends of financial efficiency and activity. Depending on the context of sampled countries, the appropriate role of policy has always been either to stem the tide of capital flows or encourage them. Policymakers who have been viewing their challenges exclusively from the latter perspective for benefits in growth (finance) might be getting the financial dynamics badly wrong. Originality/value Blanket financial development policies may not reap the financial benefits of financial globalization until domestic financial dynamics of depth, efficiency, activity and size are critically considered. The introduction of the last three previously missing components in the literature sheds more light on the globalization-development nexus.
Keywords: F02; F21; F30; F40; O10; 330; Banking; International investment; Financial integration; Development